KREASI PATUNG KERAMIK LANDSCAPE SEBAGAI PENDUKUNG ARTISTIK PADA OBJEK WISATA MELALUI PROGRAM KEMITRAAN DESA WISATA SELOREJO - Ponimin, Ponimin (Studi Budaya Nusantara, 2020)
Ceramic material landscape statue design process with “Mother and Children Harvesting Oranges” theme has purpose to strengthen Selorejo village potential as tourism village. Activity was done through PPDM LP2M UM Village Partnership Program to drive partner community creativity. Program method includes preparation, application, and evaluation. (1) Preparation includes coordination with local tourism village administrators to produce concept and design of artistic landscape statue artwork by using terracotta ceramic, cement and sand. (2) Application includes preparation of tool and material for statue artwork creation process through collaborative work between PPDM UM team and village tourism administrator team, until displaying process in tourism object and artwork finishing. (3) evaluation is by searching feedback critics by PPDM LP2M UM team and village partner to the creative activity, and this evaluation result is used as improvement tool. This activity produce one set of landscape statue artwork which displayed in Selorejo tourism village region which is located in Dau subdistrict, Malang regency.